Analisis Tingkat Literasi Keuangan Perempuan Single Parent RW 08 Depok 2 Timur - Dhona Shahreza; Lindiawatie Lindiawatie (Universitas Indraprasta PGRI, 2020)
Single parent women experience the role change not only as a housewife; nurturing, protecting and educating children but also as a head of family. This research aims to: 1) Analyse financial literacy of single parent women in RW 08 Kelurahan Abadijaya Depok 2 Timur; and 2) Investigate the differences of financial literacy among single parent women based on age, educational background, marital status, work experience and income. Kuantitative descriptive method is employed and 50 samples are taken. Data are collected by observation, questionnaire, interview and library research. The results are: 1) Financial literacy of single parent women in RW 08 Kelurahan Abadijaya Depok 2 Timur are less literate; and 2) financial literacy of single parent women are different based on age, educational background, work experience and income while marital status remains the same.